2020
DOI: 10.3390/dermatopathology7030010
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferon Signature in Chilblain-Like Lesions Associated with the COVID-19 Pandemic

Abstract: Contemporarily to the new SARS-CoV-2 mediated COVID-19 pandemic, a rise in patients with acral chilblain lesions has been described. They manifest late after mild disease or asymptomatic exposure to SARS-CoV-2. Their pathogenic evolution is currently unknown. In biopsies from three patients with acral partially ulcerating chilblain lesions that occurred associated to the COVID-19 pandemic, we analysed the expression of type I interferon induced proteins and signal transduction kinases. Histology demonstrated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Further, MxA, one of the type I interferon signatures, was highly expressed in the epidermis, cell infiltrates and vascular endothelium ( Fig. 2 D), as previously shown in COVID-19-associated chilblain-like lesions [ 8 ].
Fig.
…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Further, MxA, one of the type I interferon signatures, was highly expressed in the epidermis, cell infiltrates and vascular endothelium ( Fig. 2 D), as previously shown in COVID-19-associated chilblain-like lesions [ 8 ].
Fig.
…”
supporting
confidence: 78%
“…Morbilliform rash is a predictable rash of SARS-CoV-2 infection [ 10 ], although skin biopsies have never found viral RNA or proteins [ 3 ], suggesting an immune activation-mediated skin response. Immunohistochemical features in our case strikingly mimicked those found in COVID-19-assocated skin lesions [ 2 , 7 , 8 ]. More importantly, our case was similar to SARS-CoV-2-associated conditions of not only skin rash such as microvascular thrombi, but also PT time elongation, the sign of coagulation abnormality [ 9 ].…”
supporting
confidence: 70%
“…They speculated that the direct infection of endothelial cells may be sufficient to induce local type I IFN induction and CLL. 7 This finding has been recently supported by Hubiche et al 6 , who demonstrated an increased IFN-alfa response in CLL patients as compared to non-CLL patients with acute COVID-19 infection. The hypothesis of a pathogenetic role of IFNs in the development of CLL is further supported by the observation that patients with chronic type I IFN activation due to rare genetic type I interferonopathies frequently develop chilblain lesions.…”
Section: Dear Editormentioning
confidence: 66%
“…15 Perniosis with MxA expression in endothelial cells and surrounding dermal and epidermal tissues has been reported in children and young adults late in the course of mild confirmed or presumed COVID-19 infection. 33,34 It is speculated that efficient induction of type-1 interferons and activation of the innate immune system quickly eradicate the virus and result in a mild infection but may cause collateral tissue damage. In critically ill patients, similar acral manifestations can occur due to severe thrombotic retiform purpura, in which abnormal MxA expression is not seen.…”
Section: Discussionmentioning
confidence: 99%